2012
DOI: 10.1523/jneurosci.3261-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Contribution of Early Visual Cortex to Short-Term Memory Consolidation: A Transcranial Magnetic Stimulation Study

Abstract: The neural correlates for retention of visual information in visual short-term memory are considered separate from those of sensory encoding. However, recent findings suggest that sensory areas may play a role also in short-term memory. We investigated the functional relevance, spatial specificity, and temporal characteristics of human early visual cortex in the consolidation of capacity-limited topographic visual memory using transcranial magnetic stimulation (TMS). Topographically specific TMS pulses were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
106
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 65 publications
18
106
2
Order By: Relevance
“…Previous findings have shown the contribution of early visual areas to visual memory related to priming [21], short-term memory [22], and working memory [15]. However, in the context of the sequential Vernier, the current findings suggest a more active participation that could be more related to mental imagery, involving a memory re-enactment of the position of the stimuli to verify its alignment [4,[23][24][25].…”
Section: Manipulation Of the Spatial Informationcontrasting
confidence: 69%
“…Previous findings have shown the contribution of early visual areas to visual memory related to priming [21], short-term memory [22], and working memory [15]. However, in the context of the sequential Vernier, the current findings suggest a more active participation that could be more related to mental imagery, involving a memory re-enactment of the position of the stimuli to verify its alignment [4,[23][24][25].…”
Section: Manipulation Of the Spatial Informationcontrasting
confidence: 69%
“…Thus, this finding again supports overlap in the mechanisms that support visual perception and visual STM (Silvanto & Cattaneo, 2010). Similarly, TMS over the region of occipital cortex that encodes an array of sample stimuli disrupts encoding and storage in STM, particularly when memory load is high (van de Ven, Jacobs, & Sack, 2012). When combined with other psychophysical and neuroimaging evidence, these data lend causal support for theories that emphasize a common role of early visual areas in supporting perception and in maintaining content-specific information during STM.…”
Section: The Sensory Recruitment Hypothesis Of Content-specific Stm Rmentioning
confidence: 99%
“…In particular, analyses of fMRI data by means of multivariate "pattern analysis" techniques have revealed that modality-specific regions retain sensory-specific working-memory representations during the delay period (see Sreenivasan et al 2014). Also, if TMS is applied to visual cortex during maintenance of visual information, there is a reduction in the performance of working memory (van de Ven et al 2012). Collectively, these and related studies converge to suggest that the maintenance of working memory does not rely on any specialized storage "buffers," but instead shares the same representational zones as retrieval from longterm memory.…”
Section: Working Memorymentioning
confidence: 99%